PENGGUNAAN ALIH KODE DALAM PERCAKAPAN PADA JARINGAN WHATSAPP OLEH MAHASISWA KNB YANG BERKULIAH DI UNIVERSITAS SEBELAS MARET - Thesa, Khodiyo; Nababan, Nababan; Marmanto, Sri (Universitas Sebelas Maret, 2017)
The aims of this research are (1) to find the types of code switching that used in what’sapp conversation by KNB students of Sebelas Maret University (2) to describe the factors of code switching by KNB students of Sebelas Maret University (3) to describe the functions of code switching by KNB students of Sebelas Maret University. This research is adescriptive qualitative research employing etnography method (analizing of domain, taxonomy, and componential) in order tofix the pattern of the culture theme. The source of data taken from the code switching conversations of KNB Students. The data are conversations of KNB students in Sebelas Maret University that joined in Sibling What’sApp Group from August until November 2016 and contain of code switching. The collecting data is conversation transcription in Sibling What’sApp group that relates with switching code.The research results were (1) the types of switching code that used by KNB students wereintersentencial switching, intrasentencial switching, and tag switching. The result of analizing research that refers to Spreadly theory or etnography theory showed that intrasentential was the dominan switching code that appear on KNB students conversation about 43% (2) the factors that caused KNB students switching the code of on their conversation were speaker, addresse speaker, topic, situation, humor, ability, technology, familiarity, and relation whereas (3) the functions of switching codes on the KNB students conversations were to familiar between the speaker and address speaker, to respect the local culture they stayed, to make easy the communication, words of technology, to rich language ability, to remind something to address speaker, to respond the questions, to begin, middle and to end the conversations, to emphasize the speaker meaning, invitation, to change formal situation to informal, perception, to express the speaker feeling, to quote the other person conversation, humor, to address specification, to ask a help, to explain the speaker meaning, and to change a topic.The result of this research showed that switching code on KNB students conversation that join on Sibling What’s App group had three types and it had the factors that can influence switching code and for each KNB students conversation had the function. Intrasentencial code is the dominan switching code because KNB students often use the switching code in words or phrase form. Keywords: KNB students, code switching, intersentential switching, intrasentential switching, tag.